Kajian Epidemiologi Pengguna Rokok Elektrik di Wilayah Kabupaten Semarang - Alfan Afandi; Veri Aji Kurniawan (Pro Health Jurnal Ilmiah Kesehatan, 2019)
The transition from conventional cigarette to electrical cigarettes has grown in the community. The level of consumption shows a fairly high increase that on average consumption by the general public. The trend and popularity of vape make most vapor (electro-skirt users) make it as one of the common community of users in the community. But the impact of the use of electric cigarettes, especially the health field needs to be considered considering that vapor products also contain some ingredients that can harm health. This study aims to examine the distribution, frequency and determinants of electronics cigarette users in the district of Semarang. The results showed that most of the respondents were male (96.8%), the highest educational background of university (52.6%). The employment status of most respondents works (71.1%). Most respondents had a non-electronic smoking history (92.1%). Most of the members of this Community are the group of heavy electronic cigarette user behavior (55.2%) and the reason for using lektrik cigarette as an alternative to quit smoking (68,4%)